Misery prefigured - Rosser, J. Allyn (Jill Allyn), 1957- (Crab Orchard award series in poetry., 2001)
In her second collection of poems, J. Allyn Rosser explores the human condition in all its gloriously valiant pathos. Misery Prefigured dwells on our continual reinventions of self and world and the restless dynamic that vibrates between them. Whether contemplating a failed marriage, a visit from God, or a pearl dropped into a bottle of Prell shampoo, Rosser's wry yet impassioned eye looks hard for a habitable and abiding truth. Alternating between deadpan and dead serious, these poems are often darkly funny, exposing the contradictions inherent in every desire. Misery P.